1993
DOI: 10.1093/carcin/14.7.1457
|View full text |Cite
|
Sign up to set email alerts
|

Lowered antioxidant enzymes in spontaneously transformed embryonic mouse liver cells in culture

Abstract: Normal embryonal mouse liver cells in culture were shown to undergo spontaneous transformation during prolonged subculture. The spontaneously transformed cells lost their anchorage dependence, as measured by a soft agar assay, and gave rise to tumors in nude mice. Accompanying this transformation, the antioxidant enzymes, copper- and zinc-containing superoxide dismutase (CuZnSOD), manganese superoxide dismutase (MnSOD), catalase (CAT) and glutathione reductase, decreased significantly in activity; the decline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…The cells were subcultured with 0.25% trypsin and 1% EDTA whenever the cultures reached con¯uence. Cells were utilized for analysis within 30 passages because it has been demonstrated that antioxidant enzyme levels did not change in tumor cells for up to 50 passages (Sun et al, 1993). For enzymatic assays, the cells were grown in 100 mm tissue culture dishes (Corning) seeded at a density of 1610 6 cells.…”
Section: Cell Culturementioning
confidence: 99%
“…The cells were subcultured with 0.25% trypsin and 1% EDTA whenever the cultures reached con¯uence. Cells were utilized for analysis within 30 passages because it has been demonstrated that antioxidant enzyme levels did not change in tumor cells for up to 50 passages (Sun et al, 1993). For enzymatic assays, the cells were grown in 100 mm tissue culture dishes (Corning) seeded at a density of 1610 6 cells.…”
Section: Cell Culturementioning
confidence: 99%
“…Cancer cells usually have low activities of two major antioxidant enzymes, CuZn superoxide dismutase (CuZnSOD) and Mn superoxide dismutase (MnSOD) (Sun et al, 1993;Oberley, 2001), and overexpression of the SODs in transformed cells has been shown to reduce both malignancy and metastatic activity (Oberley, 2001;Zhang et al, 2002). The role of ROS in hepatocarcinogenesis is supported by an electron paramagnetic resonance study on patients with chronic hepatitis and at different stages of malignant transformation (Valgimigli et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…CAT has been shown to be associated with several other disease conditions. In animal cells decreased CAT levels were observed in breast cancer, adenomas and leukemia [30].This is the first study to demonstrate a genetic difference in this CAT polymorphism and T1DM.…”
Section: Discussionmentioning
confidence: 59%
“…When a genetically engineered derivative of the peroxisomal antioxidant enzyme catalase (CAT-SKL), induced by intracerebroventricular injection of Aβ [25][26][27][28][29][30][31][32][33][34][35] in the mature rat brain, it is able to reduce the toxicity of the accumulated beta-amyloid in the brain [44]. Free radical mediated oxidative stress have long been considered to be involved in the pathogenesis of diabetic complications but could they also because protein aberrations and some pathology in cells [45].…”
Section: Discussionmentioning
confidence: 99%